The k‐ε‐fP model applied to double wind turbine wakes using different actuator disk force methods. (16th October 2014) - van der Laan, M. Paul; Sørensen, Niels N.; Réthoré, Pierre‐Elouan; Mann, Jakob; Kelly, Mark C.; Troldborg, Niels
Abstract: The newly developed k ‐ ε ‐ f P eddy viscosity model is applied to double wind turbine wake configurations in a neutral atmospheric boundary layer, using a Reynolds‐Averaged Navier–Stokes solver. The wind turbines are represented by actuator disks. A proposed variable actuator disk force method is employed to estimate the power production of the interacting wind turbines, and the results are compared with two existing methods: a method based on tabulated airfoil data and a method based on the axial induction from 1D momentum theory. The proposed method calculates the correct power, while the other two methods overpredict it. The results of the k ‐ ε ‐ f P eddy viscosity model are also compared with the original k ‐ ε eddy viscosity model and large‐eddy simulations. Compared to the large‐eddy simulations‐predicted velocity and power deficits, the k ‐ ε ‐ f P is superior to the original k ‐ ε model. Copyright © 2014 John Wiley & Sons, Ltd.